Effectiveness of Fish Scale-Derived Collagen as an Alternative Filler Material in the Fabrication of Polyurethane Foam Composites - D. Naidoo; S. C. Onwubu; T. H. Mokhothu; P. S. Mdluli; M. U. Makgobole; A. K. Mishra (Advances in Polymer Technology)
This study is based on the utilization of fish scale-derived collagen (FSC) as a potential filler material in polyurethane foam (PUF) composites. The composites were prepared with varying FSC concentrations (2.5%, 5 wt%, and 10 wt%) with the standard PUF matrix, while calcium carbonates in the standard sample (STD) were completely substituted with 50 wt% of collagen. When examining the effects of collagen concentration on mechanical characteristics, complex correlations emerge between tensile strength, elongation, tear resistance, and ductility. The results reveal that the addition of 2.5 wt% FSC increased tensile strength by 12.66% during heat aging, while the addition of 5 wt% at standard temperature increased elongation by 6.65%. Under normal conditions, collagen significantly enhanced the material’s resistance to tearing, demonstrating its potential for long-term durability. Under typical conditions, tear resistance showed notable gains, increasing by 84.85% (50 wt% FSC) and 33% (10 wt% FSC), respectively. The tear resistance, however, diminishes under heat aging for all concentrations. Morphological assessments indicate a consistent closed cell structure across all samples, with collagen potentially contributing to reinforcement. The study supports the sustainable use of fish scale-derived collagen as a filler, addressing waste management challenges and aligning with principles of environmentally conscious material development.